Pengaruh Perceived Usefulness dan Perceived Ease of Use Terhadap Consumer Purchase Intention Melalui Consumer Attitude Towards Online Shopping Sebagai Variabel Mediasi pada Consumer Shopee di Jakarta - Wijayakusuma, Steven; Nurlinda, R. A. (Economic Reviews Journal, 2025)
Amidst the rapid changes in the global economy and trade, e-commerce platforms play a very important role, it is believed that the existence of e-commerce will gradually be able to shift consumer behavior from conventional methods to online purchases. This study aims to analyze the influence of perceived usefulness and perceived ease of use on consumer purchase intentions by paying attention to the mediating role of consumer attitudes towards online shopping among Shopee e-commerce users. This study uses a quantitative approach with a sample of 140 respondents. This study uses Structural Equation Modeling (SEM) based on Partial Least Square (PLS) to test the measurement instruments and structural relationships between variables. The results of this study indicate that perceived usefulness and perceived ease of use have a positive influence on consumer attitudes towards online shopping. However, perceived usefulness and perceived ease of use do not affect consumer purchase intention.Furthermore, consumer attitudes towards online shopping have a positive influence on consumer purchase intentions. And consumer attitudes towards online shopping are proven to play a mediating role between perceived usefulness and perceived ease of use on consumer purchase intentions. Shopee is advised to improve the integration of live chat features, activate the ordering process, and improve 24/7 customer service to improve perceived usefulness, ease of use, and consumer attitudes towards online shopping, which ultimately drive purchase intentions.